2008
DOI: 10.1094/pdis-92-2-0210
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility in Viburnum to Phytophthora ramorum

Abstract: Phytophthora ramorum, the causal agent of sudden oak death on oak and tanoak and Ramorum blight or Ramorum shoot dieback on ornamentals, is a recently emerged pathogen. Viburnum is a genus of commonly grown ornamental shrubs known to be susceptible to P. ramorum. The entire genus has been placed on the P. ramorum host list. The range of susceptibility of genotypes in the genus is currently not understood. We evaluated whether or not cultivars in the genus Viburnum differ in susceptibility to P. ramorum in cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…There have been a number of published trials aimed at testing pathogen aggressiveness and host susceptibility and at comparing a variety of other phenotypic traits between clonal lineages and iso lates (1,7,15,20,35,36,40,41,51,54,58,64,65). However, these indi vidual trials have not included a representative population of isolates or a range of hosts and temperatures simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of published trials aimed at testing pathogen aggressiveness and host susceptibility and at comparing a variety of other phenotypic traits between clonal lineages and iso lates (1,7,15,20,35,36,40,41,51,54,58,64,65). However, these indi vidual trials have not included a representative population of isolates or a range of hosts and temperatures simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Under-bark inoculations of branches detached from Quercus species have been used to assess variation in resistance to ramorum blight (Dodd et al, 2005;Dodd et al, 2008b;Hüberli et al, 2006a), but in tanoaks this method frequently yields nearly invisible lesions and large measurement error, precluding its use on a large scale (Hayden and Garbelotto, unpublished data). Detached-leaf inoculations with zoospore suspensions, both wounding and nonwounding, have been used to gauge host resistance to P. ramorum in its foliar hosts (Anacker et al, 2008;De Dobbelaere et al, 2010;Grünwald et al, 2008;Hüberli et al, 2006a). But tanoak leaves, again, often develop asymptomatic infections from zoospore solutions (Hansen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed similar phenotypic differences between European and North American isolates (Brasier 2003;Brasier et al 2006;DEFRA Science and Research 2004;Grünwald et al 2008a;Hüberli et al 2006;Tooley et al 2004;Werres and Kaminski 2005). However, other studies did not report any differences on a variety of other host species Grünwald et al 2008b;Hüberli et al 2006;Tooley et al 2004;Werres and Kaminski 2005). Variation in aggressiveness among isolates within both NA1 and EU1 lineages has been documented on coast live oak seedlings, detached bay laurel leaves and Q. rubra cut stems (Brasier et al 2006;Hüberli et al 2006).…”
Section: Genotypic Characterization Of the Eu1-a2 Isolatesmentioning
confidence: 79%